Polymorphisms of the CAPN, CAST, LEP, GH, GHR, IGF-1 and MSTN loci of Colombian Creole hair x Pelibuey sheep sheep crossbreeds - Lenis-Valencia, Claudia (Array, 2020)
The objective of this study was to characterize single nucleotide polymorphisms at the Calpain (CAPN), Calpastatin (CAST), Leptin (LEP), Growth Hormone (GH), Growth Hormone Receptor (GHR), Insulin-Like Growth Factor 1 (IGF-1) and myostatin (MSTN) loci in Columbian Creole hair sheep crossed with Pelibuey sheep. In 192 individuals, the CAST and MSTN loci were genotyped by PCR-RFLP, and the CAPN, GH, GHR, IGF-1 and LEP loci by PCR-SSCP and sequences. The following parameters were calculated: allelic and genotypic frequencies, observed (Ho) and expected (He) heterozygosity, fixation index and deviations from Hardy-Weinberg equilibrium (HWE). In the CAPN locus, higher frequencies of the T allele (70%) were found with respect to C (30%) and the frequencies of the TT (46%) and TC (48%) genotypes exceeded the CC (6%) genotype. For the CAST locus, the MM genotype (83%) was the most frequent, followed by the other genotypes (MN 16% and NN 0.5%) and thus the allelic frequencies were M: 91% and N: 9%. The allele A (66%) of the LEP locus was more frequent than the G allele (34%) and the AA, AG and GG genotypes had frequencies of 43, 47 and 10%, respectively. Only two genotypes (AA 64% and AG 36%) were found in the GH locus with allelic frequencies of 82 and 18% for A and G respectively. In the locus IGF-1, the genotypes AA, GG, and AG presented frequencies of 36, 49 and 15%, respectively, with a greater presence of the G allele (56%) than A (44%). In the analysed population, the GHR and MSTN loci were monomorphic, and only the AA and MM genotypes were found in each. The CAST, GH, and IGF-1 loci showed deviations from HWE. He deficit was found only in the IGF-1 locus. The CAPN, CAST, LEP, GH, and IGF-1 loci were polymorphic with high He and excess heterozygotes, in contrast, the GHR and MST loci were monomorphic. The data presented here could be used in animal breeding programmes.